2017
DOI: 10.1186/s12879-017-2891-x
|View full text |Cite
|
Sign up to set email alerts
|

Etiologic spectrum and occurrence of coinfections in children hospitalized with community-acquired pneumonia

Abstract: BackgroundCo-infections are common in childhood community acquired pneumonia (CAP). However, their etiological pattern and clinical impact remains inconclusive.MethodsEight hundred forty-six consecutive children with CAP were evaluated prospectively for the presence of viral and bacterial pathogens. Nasopharyngeal aspirates were examined by direct immunofluorescence assay or polymerase chain reaction (PCR) for viruses. PCR of nasopharyngeal aspirates and enzyme-linked immunosorbent assays were performed to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
55
1
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 31 publications
10
55
1
2
Order By: Relevance
“…In our population, the proportion of viral infections in the cases of bronchiolitis and pneumonia was 82.6% and 70.1%, respectively. These results are in agreement with previous reports in which viral pathogens were proven in over 90% of bronchiolitis cases [21][22][23] and in 43-81% of pneumonia cases [24][25][26][27][28]. Not surprisingly, RSV was the most frequently detected etiologic agent of ALRI, identified in 37.5% of the cases (44.5% in patients with bronchiolitis and 25.1% in patients with pneumonia), with a predominance of RSV subgroup B during the three seasons.…”
Section: Discussionsupporting
confidence: 93%
“…In our population, the proportion of viral infections in the cases of bronchiolitis and pneumonia was 82.6% and 70.1%, respectively. These results are in agreement with previous reports in which viral pathogens were proven in over 90% of bronchiolitis cases [21][22][23] and in 43-81% of pneumonia cases [24][25][26][27][28]. Not surprisingly, RSV was the most frequently detected etiologic agent of ALRI, identified in 37.5% of the cases (44.5% in patients with bronchiolitis and 25.1% in patients with pneumonia), with a predominance of RSV subgroup B during the three seasons.…”
Section: Discussionsupporting
confidence: 93%
“…In the viral coinfections observed in our study, Rhinovirus/RSV was the most common combination. Jiang et al observed similar results, showing that 48.6% of viral infections were Rhinovirus/RSV codetected infections. Likewise, Asner et al showed that among 77 children with ARI and viral infection, 16.9% (12 of 77) were children with Rhinovirus/RSV codetected.…”
Section: Discussionmentioning
confidence: 64%
“…A previous study conducted in Taiwan found that RSV was the most common pathogen (41.7%), followed by MPV (27.1%), Boca (6.3%), and EV (6.3%) [33]. Some important studies investigating the epidemiology of respiratory tract infection are summarized in Table 4 [4,6,13,15,23,34,35]. RSV is always the most common pathogen in young children worldwide, but the accompanying pathogens are not always the same [4,5,7,13,36,37].…”
Section: Discussionmentioning
confidence: 99%